A reconfigurable LNA with single switched input matching network for S-band (WiMAX/WLAN) applications. Issue 10 (October 2015) - Eslahi, Hossein; Jalali, Ali; Nateghi, Saman; Mazloum, Jalil
Abstract In this paper a reconfigurable Low Noise Amplifier (LNA) which works at 2.4 GHz and 3.5 GHz frequency bands is presented. In discrete approach for designing reconfigurable circuits the switch is an undeniable part. But the number of switches can make many problems such as amount of noise factor. Here, a LNA has been introduced which has only one switch and is designed with discrete tuning technique that can show good performance at mentioned frequencies. Besides, the input matching network uses a circuit that presents relatively fixed real part in input impedance, and therefore, input matching is satisfied. Using current reuse technique causes the overall gain is set in high amount. LNA is designed using <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q68wx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />0.18μm</alternatives> CMOS technology and results of simulator express that its gain is <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q6xcg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />20.07dB</alternatives> and <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q6x78" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />21.08dB</alternatives>, <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q6mb8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />s11</alternatives> is <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q6qzr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />–22.8dB</alternatives> and <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3pxxwf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />–28.86dB</alternatives>, <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3pxxc5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />s22</alternatives> has <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q6r0t" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />−18.16dB</alternatives> and <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3pxt59" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />–27.37dB</alternatives> values, NF is <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q6m85" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2.6dB</alternatives> and <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q6ss1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3.1dB</alternatives>, and IP3 is equal to <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q6p3f" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />–2dBm</alternatives> and <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3pxwn2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />–2.1dBm</alternatives> in <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q6hkk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2.4GHz</alternatives> and <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q6zw8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3.5GHz</alternatives>, respectively. The proposed LNA consumes <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q6jfw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />11mA</alternatives> from a <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q71v7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1.8V</alternatives> supply voltage.